Counseling the Academically Gifted Children - Fadila, Fadila (International Journal of Education Research and Development, 2022)
Statistically, the number of academically gifted children is quite many who are distributed in all areas. The academically gifted children will be beneficial for themselves and other people if they can develop optimally. Many academically gifted children are successful in their lives, however, we can find some of them feel difficulties. Because of that, they need counseling services. There are some important issues in counseling, especially for academically gifted children, such as (1) divergent thinking, (2) excitability, (3) sensitivity, (4) perceptiveness, and (5) entelechy. (6) self-concept, (7) counseling with parents, and (8) underachievement. To help in facing important issues, it is needed social-personal counseling, academic counseling, and career counseling. These three counseling approaches are needed simultaneously and depend on their needs. The models and strategies of counseling for academically gifted children are therapeutic, preventive, and developmental models. The choice of models is strongly determined by the need for effective counseling, to achieve the optimal result. To establish effective counseling, it is needed counseling services conducted by professional counselors.